Talk Show Hosting Turn-Allocation Techniques in Jimmy Kimmel Live - I Gusti Ngurah Ratnadi; Putu Nur Ayomi; Putu Devi Maharani (Journal of Language and Literature, 2022)
Engaging in a conversation is crucial to people as social beings, in which turn-taking is one of its core elements. As a cooperative activity, it requires an orderly turn distribution, especially in TV talk shows where the host and the guests cooperate to distribute turns led by the host. This phenomenon can be observed in Jimmy Kimmel Live, a late-night talk show that highlights conversational activities to incorporate its entertainment bits. This study investigates turn-allocation techniques used by Jimmy Kimmel as the host of the talk show to manage a multiparty conversation with the Avengers: Endgame cast. The analysis is based on Sacks, Schegloff, and Jefferson’s theory concerning the systematics for turn-taking organization along with Lerner’s elaboration on Sacks et al.’s turn allocation. To extract the data, Jeffersonian conventions are used, then the descriptive qualitative method is exercised to analyze the data in two levels: providing context and theoretical elaboration. It is found that the host only uses current-selects-next techniques (i.e., gaze, addressing, context-tied), in which context-tied becomes the most common technique practiced creating an exclusive connection that effectively allocates turn to the prospective speaker. Other techniques: gaze and addressing are also used by mutual gaze and address term positioning. Meanwhile, self-selection techniques (i.e., starting first and overlapping talk) are absent because of the unequal share of power and role of the host compared with the guests.